Revealing administrative staff roles in primary care during the COVID-19 pandemic: a qualitative study of family physicians’ perspectives - Marshall, Emily Gard; Moritz, Lauren R.; Buote, Richard; Mathews, Maria; Lukewich, Julia; Brown, Judith Belle; Sibbald, Shannon; Munene, Abraham; Hedden, Lindsay; Ryan, Dana; Spencer, Sarah (Frontiers in Health Services, 2024)
BackgroundAdministrative staff in primary care undertake numerous tasks to support patient care delivery. Although their roles are often overlooked, administrative staff are essential to the coordination and operations of primary care clinics. The COVID-19 pandemic introduced additional clinical and administrative tasks, including transitioning to virtual appointments and triaging patients for urgency, changing typical workflows. In Canada, existing pandemic plans for primary care did not account for these administrative tasks, nor the support that family physicians would require to continue to provide patient access to primary care. This research seeks to describe and understand the perceptions and experiences of family physicians of their administrative staff roles in primary care during the COVID-19 pandemic, to help inform future pandemic planning.MethodsWe present findings from a qualitative case study across four regions in Canada: Vancouver Coastal health region in British Columbia, Ontario Health West region, the province of Nova Scotia, and the Eastern Health region of Newfoundland and Labrador. We conducted semi-structured qualitative interviews with family physicians (n = 68) across the four regions and thematically analysed the data.ResultsWe identified five salient themes in the data, including (1) applying public health guidelines, (2) educating patients on COVID-19 and COVID-19 services, (3) re-organizing patient visits, (4) maintaining adequate staffing, and (5) recognizing administrative staff contributions. During the COVID-19 pandemic, family physicians took on numerous additional roles to reduce the risk of transmission of the virus with the support of their administrative staff. Family physicians emphasized the challenges of maintaining adequate staffing, and the importance of administrative staff in enabling the provision of primary care.ConclusionsExisting pandemic plans do not account for increased administrative roles taken on by primary care administrative staff. Pandemic plans must include guidance for the roles taken on by primary care administrative staff, such as clinical tasks, as they will continue to play an important role in pandemic recovery. Supporting administrative staff would enhance primary care providers’ ability to manage care during pandemics, facilitate resilience, and decrease provider and administrative burnout.